Effect of nano carbonate calcium on the low temperature performance of bitumen and asphalt mixtures in acidic and alkaline moisture - Mehdi Mehdinazar; Zahra Rasouli; Gholam Hossein Hamedi (Scientific Reports)
Abstract Moisture damage becomes more problematic when accompanied by changes in water acidity caused by surface contaminants. Due to the hydrophobicity and unique mechanical properties of nano-carbonate calcium (NCC), this study evaluated the effect of NCC on improving the low-temperature performance of asphalt mixtures under acidic (pH = 5 and pH = 6), alkaline (pH = 9 and pH = 8), and neutral (pH = 7) wet conditions using mechanical and surface free energy (SFE) tests. Two types of performance grade bitumen (PG 58–22 and PG 64–16), NCC at two weight percentages of bitumen (0.3% and 0.6%), and two types of aggregates (limestone and siliceous) were used. Low-temperature mechanical tests of bitumen and asphalt mixtures were performed using the bending beam rheometer (BBR) and semi-circular bending (SCB) tests, respectively. In addition to mechanical tests, SFE, including the Wilhelm Plate (WP) and Universal Sorption Device (USD), were utilized to determine the SFE components of bitumen, aggregates, and aqueous solutions with different pH values. Applying environmental conditions decreased the debonding energy, which reduced bitumen-aggregate adhesion and increased the likelihood of cracking at low temperatures. Acidic and alkaline conditions increased the creep stiffness and reduced the m-value of bitumen, heightening the risk of low-temperature cracking. These environments also resulted in higher fracture energy and toughness, which reduced the asphalt mixture’s stress absorption capacity and resistance to crack growth, with acidic conditions having the most severe impact. Based on the test results and statistical analysis, NCC as a bitumen additive significantly increased the bitumen-aggregate debonding energy. NCC also significantly increased the fracture energy and fracture toughness parameters in acidic and alkaline environmental conditions, reducing the likelihood of thermal cracking.